Psychological empowerment, work stress and organizational commitment among academic staff in Malaysian public universities - Azizan, Farah Lina; Isa, Aflah; Afendi, Noor Afzainiza (2015)
The purpose of this study is to investigate the significant impact on the relationship between psychological empowerment, work stress and organizational commitment among academic staff in public universities. A total number of 297 academic staff in northern region public universities in Malaysia was responded to this study. Data was analyzed using SPSS 21 to test the hypotheses of the study.The results indicated that psychological empowerment and work stress have significant impact on organizational commitment. Future research can be done by identifying other factors such as work-life balance, job overload, job security, pay and benefits, communication and work conflict that effect employee’s commitment towards organization. It is also recommended that this study could be further extended to compare between public and private universities as well.